Digital Finance Influence for MSMEs in Indonesia - Afifah Zahroh Nurjannah; Berlian Thaeba Noevus; Husnia Salsabila Fathya (Proceedings Series on Social Sciences & Humanities, 2022)
This article discusses the impact of digital finance on Micro, Small and Medium Enterprises (MSMEs) in Indonesia. With a qualitative approach, this article emphasizes the literature study method. This article aims to provide information related to how digital finance affects MSMEs in Indonesia. Based on the results of research conducted, the existence of digital finance has a significant impact on MSMEs in Indonesia, because digital finance provides several benefits including being able to save time, minimize errors in calculations, data and information security will be more secure, and can facilitate business financial management.